65-57 Court Street, June, 1962 - Shwachman, Irene (Tufts Archival Research Center, 2005)
Street-level view looking east northeast of (left to right) 65, 59, and 57 Court Street from intersection of Tremont Street. In the foreground pedestrians are crossing the street while cars wait on Court Street. A policeman is standing in the lower right corner of the image. Several signs for businesses in the area can be seen affixed to buildings including one for Patten's Restaurant. 11 x 14 Photographs